Fifty Years of Development Economics: From Planning to Liberalization Essay in Honour of Prof. P.R.Brahmanande (Malaysian Management Journal, 2000)
Fifty Years of Development Economics, Essays in HonÂour of Professor P.R. Brahmananda, Editors A. Vasedevan, D.M. Nachane, A.V. Karnik, Foreword Lord Meghnad Desai, Himalaya Publishing House, Mumbai 400 004, First Edition - 1999. This Volume is a collection of 30 essays, writÂten in honour of Professor P. R. Brahmananda, a disÂtinguished economist in India. The essays in this book focus on a number of issues such as theory and measÂurement, Indian policy framework, snictural reforms, regional perspectives and provide rich insight on variÂous subjects. The book also documents empirical studÂies researched by well-known economists. The first part of the book with 8 chapters deals with theory and measurement of money, inflation etc.. In this part, Nachne's paper on "Commodity StandÂards: Resurrection of a Classical Theme" revisits the issues relating to the concept of money standard and questions, the role of the Govenment in controlling money. The author, while reviewing the role of govÂernment in controlling the monetary policy in historiÂcal retrospection, examines a umber of alternative proposals. He chooses, amongst others, commodity standard, and analyses it to find out its relevance to modetary policy. His contribution lies in explaining the Black-Fama-Hall (BFH) model-Commodity Basket Model. This model has been discounted as it does not take into account expextations and has difficulties in choosing the commodities for the basket. The BFH model has a few advantages like a stable unit of acÂcount, subjects the government to financial discipline, can stipulate financial innovations and can insulate the economy from cyclical fluctuations originating domesÂtically. Nachne's contribution lies in simplifying the analysis on the difficult subject. Inflation has been a long drawn riddle in many countries like Brazil, Turkey, India. Control of inflaÂtion has been enforced in many countries to bring macro economic stability with high economic growth. Vasudevan, Bhoy and D hall have tried to trace equiÂlibrium between inflation and growth rate in the InÂdian context. They reached a conclusion that inflation, growth trends and their volatility, when analysed siÂmultaneously, reveal that a moderate rate of inflation on an average centered between 6 to 8 per cent in InÂdian economy with low volatility, led to high growth rates. The authors have used regression robust error technique after taking recourse to a number alternaÂtive empirical modes as suggested in the literature. The findings of the present exercise indicate that the threshÂold rate of inflation in the Indian context could be about 6 per cent; the output neutral inflation could be 4 per cent. The output effects are positive but marginally different from one another for the 5, 6 and 7 per cent inflation regimes. The negative output effects occur after 10 per cent inflation rate.